PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA KEDAI DEN BEI KOTA BEKASI - Linda Stefani; Imam Wibowo (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
This research is about The Effect of Service Quality and Price on Customer Satisfaction. This research aims to determine the simultaneous and partial effect between Service Quality and Price on Customer Satisfaction at Kedai Den Bei in Pondok Gede Bekasi. In this research the sample took 60 respondent using random sampling technique. The data that has been obtained tested using multiple linear regression analysis technique. The result that shown from this research are Service Quality and Price simultaneous and partial gave positive and significant effect on Customer Satisfaction, whereService Quality has more dominant effect to Customer Satisfaction. Thus, it can be concluded that Service Quality and Price influence Customer Satisfaction at Kedai Den Bei in Pondok Gede Bekasi.